Screening and detection of posture defects in children - Skrętowicz, Mateusz; Panek, Eliasz; Jasłowski, Damian; Rzeszutko, Mateusz; Raczkiewicz, Przemysław; Panasiuk, Dominika; Szponarowicz, Patrycja; Snopkowski, Bartosz; Korzec, Tomasz; Sosnowski, Jakub (Journal of Education, Health and Sport, 2023)
With the increasing incidence of posture defects in children and adolescents, screening of children's postures in early school periods and in the second stage of education, which is carried out, among others during routine visits to the doctor and during the balance sheet examination, is gaining significance. Early detection of the defect, at the stage of functional changes, enables full recovery, using non-invasive methods, prevents the formation of secondary changes and protects against their consequences, which significantly improves the comfort and quality of life in adulthood